Potential of Eurycoma longifolia, Curcuma zedoaria, and Allium sativum extracts as phytobiotics for shrimp health - Mohamad Iqbal Kurniawinata; Sukenda Sukenda; Dinamella Wahjuningrum; Widanarni Widanarni; Julie Ekasari (Jurnal Akuakultur Indonesia)
This study evaluated the efficacy of Eurycoma longifolia, Curcuma zedoaria, and Allium sativum in improving the immune response and resistance of whiteleg shrimp to prevent Vibrio parahaemolyticus infection. The study consisted of two phases, an in vitro phase to determine the compounds contained in three medicinal plants as antibacterials, followed by an in vivo phase to evaluate the effect of the medical plant extract on immune response and robustness against V. parahaemolyticus. The results from the first phase revealed that bioactive compounds present in E. longifolia were more varied and had higher concentrations with a lower bactericidal value when compared to those found in C. zedoaria or A. sativum. In the second phase of the experiment, the medicinal plant extract was added to the feed with a dose that was determined according to the first phase results. The treatments tested in the second phase were 1.6% E. longifolia extract dietary addition (EL16), 6.4% C. zedoaria extract dietary addition (CZ64), 6.4% A. sativum extract dietary addition (AS64) and phytobiotics mixture of 1:1:1 (C1) dietary addition, as well as no phytobiotic for negative control treatment and positive control. The results from the second stage demonstrated that dietary phytobiotic extract addition enhances the immunological responses and improves the shrimp survival against V. parahaemolyticus challenge compared to the control group. In conclusion, E. longifolia, C. zedoaria, and A. sativum showed different bioactive compound profiles, which affect their efficacy against V. parahaemolyticus, with EL16 showing higher efficacy.